1981
DOI: 10.1037/0021-9010.66.3.385
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of some aspects of the Steers and Rhodes model of employee attendance.

Abstract: This study examines the relationships between production employee absenteeism and personal characteristics, job situation, and job satisfaction. The Steers and Rhodes hypothesized model of employee attendance suggests that these variables are major influences on absenteeism. The time-lost measure of absence was used for the dependent variable. Multiple regression and the general linear models approach to hypothesis testing were used in the analyses. The results indicate some statistically significant and some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

1989
1989
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 13 publications
1
26
0
1
Order By: Relevance
“…Although some authors have questioned whether job alternatives actually influence individual-level responses to dissatisfaction (Hulin, Roznowski, & Hachiya, 1985), existing studies using measures such as ease of movement (Landau & Hammer, 1988), un-employment rates (Carsten & Spector, 1987), information regarding job choices (Caldwell & O'Reilly, 1985), and the value placed on nonwork time (Youngblood, 1984) have supported the claim that good job alternatives promote active responses to dissatisfaction. Also, the possession of higher-quality alternatives appears to be associated with greater tendencies toward voice behaviors such as whistle-blowing (Miceli & Near, 1984), grievance filing (Fleishman & Harris, 1962;Muchinsky & Maassarani, 1980), and constructive social movements (Lammers, 1969;Zald & Berger, 1978), with lesser tendencies toward loyalty behaviors such as job commitment (McLaughlin & Butler, 1974;Pfeffer & Lawler, 1980), and with lesser tendencies toward neglectful acts such as absenteeism and slow-down behaviors (Behrend, 1953;Crowther, 1957;Larson & Fukami, 1985;Owens, 1966;Watson, 1981).…”
Section: Predicting the Responsesmentioning
confidence: 96%
See 1 more Smart Citation
“…Although some authors have questioned whether job alternatives actually influence individual-level responses to dissatisfaction (Hulin, Roznowski, & Hachiya, 1985), existing studies using measures such as ease of movement (Landau & Hammer, 1988), un-employment rates (Carsten & Spector, 1987), information regarding job choices (Caldwell & O'Reilly, 1985), and the value placed on nonwork time (Youngblood, 1984) have supported the claim that good job alternatives promote active responses to dissatisfaction. Also, the possession of higher-quality alternatives appears to be associated with greater tendencies toward voice behaviors such as whistle-blowing (Miceli & Near, 1984), grievance filing (Fleishman & Harris, 1962;Muchinsky & Maassarani, 1980), and constructive social movements (Lammers, 1969;Zald & Berger, 1978), with lesser tendencies toward loyalty behaviors such as job commitment (McLaughlin & Butler, 1974;Pfeffer & Lawler, 1980), and with lesser tendencies toward neglectful acts such as absenteeism and slow-down behaviors (Behrend, 1953;Crowther, 1957;Larson & Fukami, 1985;Owens, 1966;Watson, 1981).…”
Section: Predicting the Responsesmentioning
confidence: 96%
“…Research on continuance commitment has indicated that high levels of personal sacrifice increase attitudinal commitment and likelihood of staying (McGee & Ford, 1987;Meyer, Allen, & Gellatly, 1990). Voice behaviors such as making job suggestions and grievance filing have been linked with investments such as seniority and prior promotions (Price et aL, 1976;VanZelst & Kerr, 1953); loyalty responses such as commitment, positive work attitudes, and good citizenship behavior have been shown to be linked to psychological and material investments (Arkes & Blumer, 1985;Buchanan, 1974;Meyer & Allen, 1984); quitting and intent to quit appear to be inhibited by greater length of service, identification with a job, and job training (Ferris & Aranya, 1983;Guzzo, Jette, & Katzell, 1985;Koch & Steers, 1978;Rusbult & Farrell, 1983;Wanous, Stumpf, & Bedrosian, 1979;Werbet & Gould, 1984;Youngblood, Mobley, & Meglino, 1983); and neglect responses such as absence, lateness, and lack of effort seem to be inhibited by investments such as cross-training, work-connected recreational programs, and home ownership (Pascale, 1978;Watson, 1981). Also, sunk costs have been shown to increase the propensity to persist with a course of action in the face of negative information (Garland, 1990).…”
Section: Predicting the Responsesmentioning
confidence: 96%
“…A complete test of the model has not been reported to date (Rhodes & Steers, 1990). Moreover, partial tests have provided only mixed support for the model (e.g., Hammer, Landau, & Stem, 1981;Watson, 1981). This suggests that factors affecting absenteeism vary depending on the work situation, attendance policies, and worker characteristics in the organization.…”
Section: Perceived Ability To Attendmentioning
confidence: 99%
“…Misalnya, Steers dan Rhodes (1978) dan Watson (1981) menemukan bahwa para karyawan perempuan absen dari kerja lebih banyak daripada laki-laki. Penelitian oleh van der Velde (2003) menunjukkan laki-laki memiliki komitmen organisasional lebih tinggi.…”
Section: Hipotesis Penelitianunclassified